The Generalized Correlation for Friction Factor in Criss-cross Flow Channels of Plate Heat Exchangers - Arsenyeva, O. P.; Tovazhnyanskyy, Leonid Leonidovich; Kapustenko, P. O.; Khavin, G. L. (The Italian Association of Chemical Engineering, 2011)
The paper concerns with analysis of the influence of corrugation form of PF1E plates on hydraulic resistance in the formed channels. The data for models of the main corrugated field of the inter-plate channel considered. It enables to exclude the influence of entrance and exit distribution zones. The specific type of generalizing formula is used, which correlates the data in a wider range of Reynolds numbers, compare to conventional ones. The equation for hydraulic performance of inter-plate channels with sinusoidal and triangular corrugations shapes is obtained, which generalizes experimental data of different authors available in literature. It accounts for the influence of the corrugation inclination angle to the plate vertical axis and corrugations pitch to height ratio.